(untitled) (Agroindustrial Science, 2023)
The terrestrial entomofauna was determined in the La Arena sector, Huamachuco, Perú; for this, the workplace was divided into 3 zones; previus, middle and rear. For the collection of insects, Pitfall traps, striking nets and aerial nets were used in a transect of 100 linear meters and 5 repetitions. The collected samples were processed in the entomology laboratory of the National University of Trujillo, determining 27 families belonging to 6 insect orders. The comparison of insect diversity with the Margalef index was made; for the previus and rear area with 1.93 and 1.94, respectively. In relation to the Simpson index, the values obtained were 0.13, 0.19 and 0.15, for the rear, middle and previus zones; likewise, the values of the Shanon-Weaver index for the rear, middle and previus zones with 7.69, 5.26 and 6.67, respectively. In addition, to measure the similarity between the sampled areas, the Jaccard (47.83%), Sorensen (66.72%) y Morisita-Horn (69.71%) indices were applied, presenting the highest value between the middle and posterior area. It is concluded that there is a high diversity of terrestrial entomofauna in the surroundings of the La Arena mine, Huamachuco, Peru, with several species related to each other.